The effect of SiC reinforcement on tribological behaviour of cold sprayed coatings in water - Deprem, Ozde; Paksoy, Ahmet Hilmi; Tazegul, Onur; Cimenoglu, Huseyin (SAGE Publications, 2017)
AbstractIn this study, structural characteristics and tribological performance of the coatings deposited on a 1050 quality aluminium substrate by cold spraying of the feedstock consisting of 100% Al–12Si and 25 vol.% SiC + 75 vol.% Al–12Si powders were examined. Wear tests were conducted in air and in water against alumina ball under loads of 1 and 5 N by a reciprocating wear tester at room temperature. Presence of SiC particles in the structure enhanced the wear resistance of the Al–12Si coating both in air and water. As compared to the air testing condition, water containing media provided better tribological performance especially at the wear test load of 1 N. The findings of this study revealed potentiality of water to be used as a lubricant for SiC-reinforced Al–12Si matrix cold spray composite coatings at relatively low wear test loads.